Diateichismata Zu dem Phänomen innerer Befestigungsmauern im griechischen Städtebau - Sokolicek, Alexander (Österreichisches Archäologisches Institut, 2009)
A Diateichisma is part of a city´s fortification system. Unlike a city wall it was built within the urban area dividing a city in two parts. This study focuses on two aspects. On the one hand, the phenomenon of diateichismata is considered as part of fortification architecture, on the other hand the influence of diateichism on the organisation of the urban space is pointed out. Furthermore, the reasons, why diateichismata were build are considered as a focal point of the study. The settlement are displayed in a catalogue, technical data is in charts. Written sources mentioning diatechisma are put together including relevant passages of the text. In scientific research diateichismata have been regarded as mere functional buildings, however, they have been studied systematically. In this study, the significance of diateichismata is analysed beyond the aspects of fortification; in particular, the impact of diateichismata on the development and utilisation of urban space is a spezial interest. A comparative analysis of settlements with diateichisma has needs of comparable criteria. The most applicable term, after which settlements with diateichisma can be discerned and put in order, is the chronological relation of diateichisma and city wall, because here chronology is the only variable giving valuable information on settlement development. Hence three variations of settlements with diateichisma can be discerned: 1. Settlements with diateichisma built together with the enceinte. 2. Settlements with secondarily but diateichisma. 3. Settlements with diateichisma which originate after expansion of walled urban space. Most of the studied settlements have diateichismata which were built after the enceinte (23 examples) or which origins from expansion of walled city space (19 settlements). Contemporaneous diateichismate are rare (14 settlements), only in a few cities the relation between diateichisma and city wall remains unclear. The earliest diateichismata be dated in late 7th cent. B.C., the latest was build in the middle of the 2nd cent. B.C. Within this chronological frame the highest concentration of diateichismata can be traced in classical and hellenistic times. The distriution of cities is spead from the Iberian Peninsula to Greek parts of modern Afghanistan (Graeco-bactria). Only any regions do show concentrations of settlements with diateichisma. In the Western Mediterranean there are more cities with secondarily built diateichisma, in the area of north-western Greek in a lot of cities the walled urban space was enlarged establishind diateichismata between the original city area and the newly acquired space. Generally, diateichismata serve as obstacles to enemies which conquered the enceinte already or as barrier wall for hostile parties fighting within the boundaries of the city wall. Despite of the clear military function only cities of military character have a diateichisma; there it always serves as a barrier wall protecting free space